2010
DOI: 10.1111/j.1365-2133.2010.09887.x
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of cancer in the general population and in patients with or without atopic dermatitis in the U.K.

Abstract: Our results indicate an increased incidence of cancer overall as well as of specific cancer subtypes, including lymphoma, in patients with AD. Further studies are needed to disentangle the effects of treatment for AD from AD itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 28 publications
6
90
1
1
Order By: Relevance
“…The latter study also showed a reduced risk of multiple myeloma in asthmatic women (SIR = 0.53). A significant inverse association between asthma and leukemia was also reported by Turner et al [12] (RR = 0.75), whereas two further studies showed a positive association between lymphoma and atopic dermatitis; one calculated an SIR of 2.0 whilst the other presented an IRR of 2.21 [20,21]. In a further study, where hematological malignancy was not specified, allergic rhinitis turned out to be a risk factor too (SIR = 1.23) [15].…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The latter study also showed a reduced risk of multiple myeloma in asthmatic women (SIR = 0.53). A significant inverse association between asthma and leukemia was also reported by Turner et al [12] (RR = 0.75), whereas two further studies showed a positive association between lymphoma and atopic dermatitis; one calculated an SIR of 2.0 whilst the other presented an IRR of 2.21 [20,21]. In a further study, where hematological malignancy was not specified, allergic rhinitis turned out to be a risk factor too (SIR = 1.23) [15].…”
Section: Resultsmentioning
confidence: 74%
“…They found a slightly increased risk of cancer for asthmatic men (SIR = 1.12), whereas González-Pérez et al [18] reported no association. A positive association between atopic dermatitis and cancer risk was observed in a prospective study in Denmark (SMR = 1.5) as well as in a retrospective cohort study in Sweden observing 15,666 patients hospitalized for atopic dermatitis (SIR = 1.13), and a study in the UK (IRR = 1.49) [19,20,21]. Three further studies could not describe any correlation between a history of allergy and either cancer in general or any specific cancer site [22,23,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Legendre et al (2015) performed a meta-analysis of 4 cohort studies and 18 case-control studies, and found a modest increase in risk of lymphoma in patients with AD compared with the general population (43). The increased risk was statistically significant in the meta-analysis of the cohort studies (RR 1.43, 95% CI, 1.12 -1.81) (24,(44)(45)(46). In the meta-analysis of the case-control studies the increased risk for lymphomas was insignificant (OR 1.18, 95% CI 0.94 -1.47) (43).…”
Section: Atopic Dermatitis Per Se and Increased Risk For Lymphomamentioning
confidence: 99%
“…− The second one proposes a relation between atopy and an increased risk of neoplastic diseases, stemming from chronic stimulation of the immunological system [1,2,3]. According to the first hypothesis, the overstimulation of immunocompetent cells, which results from contact with an allergen, causes the production of certain IgE antibodies that may have a cytotoxic influence on neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%